Menyelami Tren Populasi Dunia: Fakta, Angka, dan Implikasinya - Ninawati; Fransiska Liska; Veronika Tiara; Yusawinur Barella (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
World population conditions are the main focus in understanding global social and economic dynamics. This article reviews trends in world population in the last five years, taking into account population growth and the factors that influence it. Apart from that, the analysis also focused on the 10 countries with the largest population in 2023. An investigation was carried out into the causes of the high population in these countries and the resulting consequences, both from a social, economic and environmental perspective. By exploring the latest data and information, this article aims to provide a comprehensive picture of global population dynamics and its implications for the future.